2013
DOI: 10.1186/1749-7922-8-28
|View full text |Cite
|
Sign up to set email alerts
|

Acute intraperitoneal rupture of hydatid cysts: a surgical experience with 14 cases

Abstract: IntroductionHydatidosis is endemic in the Mediterranean region including morrocco, the Middle and Far East, Australia, New Zealand, and South America—all areas where animal husbandry is common. Rupture into the abdominal cavity is a rare but serious complication of hydatid disease. The cysts may be ruptured after a trauma, or spontaneously as a result of increased intracystic pressure. Rupture of the hydatid cyst requires emergency surgical intervention.MethodsFourteen patients received surgical treatment for … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
50
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 38 publications
(50 citation statements)
references
References 19 publications
0
50
0
Order By: Relevance
“…Studies from Bahir Dar, Northern Ethiopia, and Addis Ababa showed HC to be more common in the third decade of life (21–30 years) with a mean age of 37 and 33.5 years, respectively [ 3 , 6 ]. Studies from Iran and Morocco found a mean age of 40 years and 39.5 years, respectively [ 10 , 16 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Studies from Bahir Dar, Northern Ethiopia, and Addis Ababa showed HC to be more common in the third decade of life (21–30 years) with a mean age of 37 and 33.5 years, respectively [ 3 , 6 ]. Studies from Iran and Morocco found a mean age of 40 years and 39.5 years, respectively [ 10 , 16 ].…”
Section: Discussionmentioning
confidence: 99%
“…The study in Bahir Dar found 79.2% of the patients to have liver HC [ 3 ]. In the liver, the right lobe as the most common site affected was reported by studies from Addis Ababa, Tehran, and Morocco, which showed right lobe affected in 55.5%, 75%, and 50% of the patients, respectively [ 6 , 10 , 16 ]. Liver is the most commonly affected organ because it is the first organ which takes parasite infested portal venous system [ 2 ].…”
Section: Discussionmentioning
confidence: 99%
“…After confirming the diagnosis of intraperitoneal rupture, medical treatment should be initiated with fluid resuscitation for stabilizing hemodynamic status and treating anaphylactic reactions with corticosteroids, antihistaminic, and vasopressor drugs. Emergency surgery remains the treatment of choice in Intra peritoneal rupture of Hydatid cyst [2][3][4][5]. Here we share our experience of a case of giant hydatid cyst of liver with spontaneous rupture and challenges faced in its management.…”
Section: Introductionmentioning
confidence: 88%
“…Peritoneal fluid recognition is recommended during the first evaluation of trauma patients [38] as well as in patients presenting with several abdominal complaints and shock [39, 40]. When the abdomen is evaluated in left coronal views, a full stomach appearing below the diaphragm may mimic a condition of peritoneal fluid (Fig.…”
Section: Introductionmentioning
confidence: 99%